Rekonstruksi Konsep Kesetaraan Gender dalam Hukum Islam: Studi Kritis terhadap Kepemimpinan Perempuan dan Pembagian Warisan - Taqwim, Andi Ahsan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article discusses the concept of gender equality in the perspective of Islamic legal thought, by examining the central issues that are about to become contentious in contemporary Muslim societies. The research uses a qualitative approach with a literature study method, examining the major literatures of modern Islamic figures and thinkers as well as analyzing the Shariah evidence. The focus of study includes three main issues: the principle of gender equality in Islamic law, women’s leadership in public and private spaces, as well as the debate around the division of inheritance between men and women. Discussion results show that although religious texts normatively give recognition to the spiritual and moral equality between men and women, in practice differences of interpretation bordering on pros and cons still occur among Muslim scholars and scholars. This study concludes that a contextual understanding of the nash-nash of sharia as well as the maqashid approach of sharia is necessary to realize gender justice in contemporary Muslim societies.